Solitary Plasmacytoma of Skull: A Rare Cytological Diagnosis - Gill, Manmeet Kaur (JCDR Research and Publications (P) Limited, 2013)
Solitary Plasmacytoma of the Skull (SPS) is very rare and only 35 cases have been reported in the English literature. It remains controversial whether a solitary plasmacytoma of the skull is essentially identical with a Solitary Plasmacytoma of Bone (SPB) or not. A solitary plasmacytoma of bone, which includes a solitary plasmacytoma of the skull, is characterized by a radiologically solitary bone lesion, neoplastic plasma cells in the biopsy specimen, fewer than 5% plasma cells in bone marrow, less than 2.0 g/dl monoclonal protein in the serum when it is present and a negative urine test for Bence Jones protein (monoclonal light chain). A solitary plasmacytoma of bone tends to disseminate or progress to multiple myeloma, even as long as 7-23 years after its presentation.